Review article The role of perception in loanword phonology - Michael Kenstowicz (Studies in African Linguistics, 2003)
Review Article: The Role of Perception in Loanword Phonology. A review of Les emprunts linguistiques d'origine europeenne en Fon by Flavien Gbeto, Koln: Rudiger Koppe Verlag, 2000